Perancangan Sistem Informasi Penerimaan Santri Baru Berbasis Web Dengan Pendekatan UML - Abdiansyah, Zeldi; Juansen, Monsya; Gunawan, Gunawan; Lala, Andi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Markaz Abu Bakar in Bengkulu City is a private educational institution that provides education from early childhood (PAUD) to junior high school (SMP). The student admission process at this institution is still conducted manually, which leads to several issues such as long queues, data recording errors, administrative delays, and low efficiency in time and labor. To address these problems, the implementation of a web-based information system is necessary. This study aims to design a web-based new student admission information system using the Unified Modeling Language (UML) approach, which includes four main diagrams: Use Case, Class, Sequence, and Activity Diagram. The methodology used is Design Science Research (DSR), which consists of problem identification, artifact design, demonstration, and evaluation. Data were collected through observation, interviews, and literature review. The result of this study is a system design that facilitates online registration, including form submission, document uploads, and online payment processes. The system is intended to improve efficiency, effectiveness, and transparency in school administrative management. With this system, parents and prospective students do not need to visit the school in person, making the registration process faster and more convenient. The proposed system is expected to be accessible, secure, and capable of simplifying data management for school staff. This research provides a practical contribution to the digital transformation of educational administration in Islamic boarding school environments.